The Role Of Student Satisfaction In The Roots Of Determining Word Of Mouth (Wom) - Aprih Santoso; Sri Yuni Widowati; Zakky Fahma Auliya (UIN Raden Mas Said Surakarta, 2021)
Abstract This study aims to determine the effect of service quality and Word Of Mouth (WOM) on student satisfaction at the University of Semarang as an Intervening Variable. The independent variable in this study is the quality of service and the dependent variable is Word of Mouth (WOM) while the Intervening Variable is student satisfaction at the University of Semarang. The research was conducted by taking a sample of 129 students of the University of Semarang. The research method uses accident sampling. The technical analysis in this study uses Path analysis. The result shows that service quality and satisfaction directly effect the Word Of Mouth (WOM) of the University of Semarang students. Service quality) has a direct influence on student satisfaction at the University of Semarang and satisfaction is able to moderate the effect of service quality on the Word Of Mouth (WOM) of of the University of Semarang students